Factors Affecting Leadership in Pharmacy Students: A Nationwide Survey - Jin HK; Kim E (Dove Medical Press, 2024)
Hye Kyung Jin,1- 3 Eunyoung Kim1,3,4 1Research Institute of Pharmaceutical Sciences, College of Pharmacy, Chung-Ang University, Seoul, South Korea; 2Department of Psychology, Seoul National University, Seoul, South Korea; 3Data Science, Evidence-Based and Clinical Research Laboratory, Department of Health, Social, and Clinical Pharmacy, College of Pharmacy, Chung-Ang University, Seoul, South Korea; 4Division of Licensing of Medicines and Regulatory Science, The Graduate School of Pharmaceutical Management, and Regulatory Science Policy, The Graduate School of Pharmaceutical Regulatory Sciences, Chung-Ang University, Seoul, South KoreaCorrespondence: Eunyoung Kim, Data Science, Evidence-Based and Clinical Research Laboratory, Department of Health, Social, and Clinical Pharmacy, College of Pharmacy, Chung-Ang University, 84 Heukseok-ro, Dongjak-gu, Seoul, 06974, South Korea, Tel +82-2-820-5791, Fax +82-2-816-7338, Email eykimjcb777@cau.ac.krPurpose: Leadership is increasingly becoming a priority in the forms of higher education associated with the Fourth Industrial Revolution; however, few studies have examined it in the context of pharmacy education. This study investigated the levels of communication competence, critical thinking disposition, problem-solving ability, and leadership of pharmacy students, and identified factors related to leadership.Methods: This study was conducted using a nationwide cross-sectional online survey with a self-administered questionnaire. A total of 416 third-to-sixth-year pharmacy students from all 35 pharmacy schools in South Korea, completed the survey from September 1 to 15, 2019. Data were analyzed using descriptive statistics, t-tests, Pearson's correlations, and multiple regression analysis. We verified construct validity by performing an exploratory factor analysis.Results: The pharmacy students revealed a moderate level of communication skills, critical thinking disposition, problem-solving ability, and leadership. Significant positive correlations were found among communication competence (r=0.724, p< 0.001), critical thinking disposition (r=0.615, p< 0.001), problem-solving ability (r=0.599, p< 0.001), and leadership. After adjustment for control variables, communication competence (β=0.319, p< 0.001) was found to be the most significant predictor of leadership (F=104.12, p< 0.001, R2=0.756).Conclusion: This study showed that the students' leadership was influenced by their competence in communicating effectively, thinking critically, and solving problems. Pharmacy educators should acknowledge and implement innovative curriculum and assessment approaches in preparing pharmacy students for their professional paths.Keywords: leadership, communication competence, critical thinking disposition, problem-solving ability, pharmacy students